Determination and validation of G-factor for plastic manifolds - Mohammed, Thamer Ahmed; Ghazali, Abdul Halim; Megat Mohd Noor, Megat Johari; Mohd Soom, Mohd Amin (Federation of Engineering Institutions of Islamic Countries, 2006)
G-factor is used to compute the head loss due to friction in manifolds. There are many formulae derived to compute the G-factor for manifolds. But most of these formulae were derived based on the theoretical basis with assumptions. The formulae of G-factor can be divided into two types. The first type was based on the location of the first outlet from the beginning of the manifold length while the second type was based on the end condition of the manifold (open or closed). In this study, a test rig was fabricated in order to validate formulae for G-factor. The rig consisted of an elevated tank, plastic manifolds, piezometers, and pump. Beside checking the effect of the manifold size, outlet spacing and end condition on the G-factor, the most accurate formula for computing G-factor is recommended.